Selling & Collecting : Printed Book Sale Catalogues and Private Libraries in Early Modern Europe - Granata, Giovanna; Nuovo , Angela; Granata, Giovanna; Nuovo , Angela (eum edizioni universita di macerata, 2018)
Based on the contributions given at a conference held at the University of Cagliari in September 2017, this collection of essays provides an insight into the distribution and acquisition of printed books in the sixteenth and seventeenth centuries. Publishers$1 (Band booksellers$1 (Bcatalogues are examined as evidence of the advertising and selling techniques used by agents in the book trade, with a focus on book prices. The role of sixteenth-century private libraries and the growing phenomenon of book collecting are studied within a commercial frame. In this context, private collections are investigated as places of preservation rather than consumption, of the works being circulated within the book trade.s
English
Keywords: Literature & literary studies; distribution; acquisition; printed books; sixteenth century; seventeenth century; Currency; Denarius; Italy; Perugia; Veneto; Venice